Incidence and Predictive Factors for Additional Opioid Prescription after Endoscopic Skull Base Surgery - Shen, Sarek A.; Jafari, Aria; Qualliotine, Jesse R.; DeConde, Adam S. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Introduction Postoperative pain management and opioid use following endoscopic skull base surgery (ESBS) is not well understood. A subset of patients requires additional opioid prescription (AOP) in the postoperative period. The objective of this study is to describe the incidence of AOP, as well as evaluate patient and surgical characteristics that may predict additional pain management requirements following ESBS.Methods A retrospective review of cases undergoing ESBS between November 2016 and August 2018 was performed. We reviewed patients' sociodemographic and clinical data, and Controlled Substance Utilization Review and Evaluation System (CURES) records. Stepwise multivariable logistic regressions were performed to evaluate the factors associated with AOP within 60 days following surgery.Results A total of 42 patients were identified. Indications for ESBS included intracranial mass (64.2%), sinonasal malignancy (23.8%), and skull base reconstruction (9.5%). AOP were recorded in nine patients (21.4%). There were no significant differences in operative factors, including approach, lesion location, or perioperative analgesia between the two cohorts. On multivariable logistic regression, we found that younger age (odds ratio [OR]: 0.891, 95% confidence interval [CI]: 0.79–1.00, p = 0.050), comorbid depression (OR: 86.48, 95% CI: 1.40–5,379.07, p = 0.034), and preoperative opioid use (OR: 104.45, 95% CI: 1.41–7,751.10, p = 0.034) were associated with additional prescriptions postoperatively.Conclusion The requirement for extended postoperative opioid pain control is common after ESBS. Patient demographics including age and psychosocial factors, such as depression may predict the need for AOP after ESBS. These results suggest that patient-driven factors, rather than surgical characteristics, may determine the need for prolonged pain control requirements after ESBS.
Keywords: opioid; endoscopic skull base surgery; pain management; outcomes; quality of life; prolonged opioid use